2011
DOI: 10.5483/bmbrep.2011.44.7.484
|View full text |Cite
|
Sign up to set email alerts
|

Transduced Tat-Annexin protein suppresses inflammation-associated gene expression in lipopolysaccharide (LPS)-stimulated Raw 264.7 cells

Abstract: Annexin-1 (ANX1) is an anti-inflammatory protein as well as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Construction, purification and transduction of the Tat-ANX1 protein was previously described (20). In this study, we investigated how transduced Tat-ANX1 protein inhibited TPA-induced skin inflammation.…”
Section: Purification and Transduction Of Tat-anx1 Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction, purification and transduction of the Tat-ANX1 protein was previously described (20). In this study, we investigated how transduced Tat-ANX1 protein inhibited TPA-induced skin inflammation.…”
Section: Purification and Transduction Of Tat-anx1 Proteinmentioning
confidence: 99%
“…Expression and purification of the ANX1 fusion proteins were carried out as described previously (20). To produce the Tat-ANX1 proteins, the plasmid was transformed into E. coli BL21 cells (Novagen, Sandiego, CA, USA).…”
Section: Expression and Purification Of Tat-anx1 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the transduction mechanism remains unclear, PTD fusion proteins have been used to deliver therapeutic proteins in vitro and in vivo. We have shown previously that various PTD fusion proteins transduced into neuronal cells cross the blood-brain barrier and efficiently protect against cell death (14)(15)(16)(17)(18)(19)(20). In this study, we investigated the protective effects of PEP-1-p18 against MPP + -induced dopaminergic neuronal cell death and MPTP-induced PD mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6-deficient (IL-6 -/-) mice are resistant to the induction of various experimental inflammatory diseases (14). The mitogen-activated protein kinase (MAPK) pathway is important for immune response and mycobacterial pathogenesis (15)(16)(17), and MAPK family members include extracellular signal-regulated kinase, p38 MAPK (p38), and stress-activated protein kinase/c-Jun N-terminal kinase (18). It has been reported that p38 was activated in monocytes following M.tb infection (19).…”
Section: Introductionmentioning
confidence: 99%